Intraoperative pyloric drainage is unnecessary during esophagectomies: a meta-analysis and systematic review of randomized controlled trials - Armand Csontos; Armand Csontos; Dávid Németh; Dávid Németh; Lajos Szakó; Lajos Szakó; Lajos Szakó; Gergő Berke; Dóra Lili Sindler; Dávid Berki; Csenge Papp; Péter Hegyi; et al. (Frontiers Media S.A., 2024)
Objective: The topic of this meta-analysis is the comparison of gastric conduit esophageal reconstructions with or without pyloroplasty.Background: Surgical procedures, especially minimal invasive esophagectomy (MIE) can be a curative treatment in the early stages of esophageal cancer. Previously, intraoperative pyloroplasty was routinely performed, but nowadays it became debated again in the light of minimally invasive esophagectomy.Methods: A comprehensive search was performed in multiple databases to identify randomized controlled trials investigating the topic. Two independent authors performed the selection based on predefined criteria. Statistical analysis was performed to assess any significant difference, then the bias and quality of the data were estimated.Results: Nine relevant RCTs consisting of 529 patients with esophageal cancer were identified. No significance was found in mortality [odds ratio (OR): 0.85; p = 0.642], anastomosis leakage (OR: 0.57; p = 0.254), respiratory morbidity (OR: 0.51; p = 0.214) and vomiting (OR: 0.74; p = 0.520), however the results about gastric emptying time (GET) were controversial (weighted mean difference (WMD): −67.71; p = 0.009, OR: 2.75; p = 0.072). Significant heterogeneity was not detected except for GET. Trial sequential analyses (TSA) show that a certain conclusion would require more data except in the binary variables of GET.Conclusion: We conclude that the pyloric drainage procedure is not routinely necessary, but further well-designed studies would be needed, especially in Europe.